PERFORMA AYAM RAS PETELUR COKLAT DENGAN FREKUENSI PEMBERIAN RANSUM YANG BERBEDA - Didik Margo Utomo (Universitas Islam Balitar, 2017)
This aims of the study is to determine the effect of different feeding frequency on layer performance (feed intake, hen day production, egg weight, and feed conversion ration) Data experiment were held on 10th April-10th July 2017 at Abas Farm, Ponggok subdistric, Blitar regency. Four hundred laying hens of ISA Brown strain age 30 weeks were used in this study and kept in individual cages. A randomized completely design was applied with 4 treatments and 5 replications. The treatment consists of P0: 2 times feeding, P1: 3 times feeding, P2: 4 times feeding, and P3: 4 times feeding. Data ware analyzed using analysis of variance at 5% level and Duncan test at 5 % level. The conclusion based on the result were: the treatments not significant (P>0.05) on feed intake, egg weight, and feed conversion ration, but significant (p<0.05) on hen day production. It ’s suggested to use 2 or 3 time feeding frequency.Keyword: feeding frequency, performance, layer.